Persistent left-sided SVC: An incidental finding during Port-A-Cath placement - Jakob Hama; Matthew Smith; Geovanna Erazo (Radiology Case Reports, 2024)
Port-A-Cath (port), a single-lumen, tunneled catheter, is routinely placed into the superior vena cava (SVC) for cancer patients undergoing chemotherapy. We present a case of a port placement in which variant anatomy was discovered during the fluoroscopy-guided procedure and confirmed by venogram of a persistent left-sided SVC (PLSVC). Upon further investigation into the patient's previous computed tomography (CT) scans, the diagnosis was further confirmed. Patients with PLSVC are typically asymptomatic; however, some are associated with increased congenital heart defects (CHD), which increase the risk for complications during invasive procedures. Diagnosing PLSVCs and knowing the clinical implications/complications can improve patient care; by not removing catheters unnecessarily and being prepared to treat/minimize complications.